Sirosis Hepatis - Hasan Darmawan; Agustina Agustina (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Hepatic cirrhosis (SH) is a disease/group of diseases that infects the liver, characterized by loss of liver lobular architecture due to fibrosis and damage to parenchymal cells and their regeneration which ultimately forms a nodular structure. According to its clinical manifestations, this disease has a long latent period but is followed by sudden abdominal swelling, abdominal pain, hematemesis, edema and jaundice. In the next phase, the most prominent symptoms include jaundice, ascites, portal hypertension, and central nervous system abnormalities that end in coma. SH is infecting the whole world. SH is the eleventh leading cause of mortality and the fifteenth leading cause of morbidity worldwide. There are many things that have been proven to cause SH, including infections, toxins, hereditary conditions, and even autoimmune processes. Some of the complications that arise from SH include gastroesophageal varices (affecting the stomach and esophagus), hypersplenism (affecting the splenic organs), hepatorenal syndrome (affecting the kidneys) and even hepatic encephalopathy (affecting the central nervous system).